The factors which influence training effectiveness at UDA Holdings Berhad / Norlia Mohamad Nadziri - Mohamad Nadziri, Norlia (Faculty of Business and Management, 2010)
This research is study on the Factors Which Influence Training Effectiveness at UDA Holdings Berhad. This is also attempts to identify the significant determinants of training effectiveness. By constructing a hypothetical research model to investigate the effect of 3 variables; trainer, training contents, and training methods (independent variable) towards training effectiveness (dependent variable), a survey questionnaire was distributed to employees in various departments on UDA Holdings Berhad who have attended training programs. Data was obtained and subjected to reliability tests using Cronbach's Alpha, and the 3 hypotheses drawn up from the research model were subjected to tests of significance correlation relationship. Out of the 3 hypotheses, it was found training method to be most significant factor influencing on training effectiveness. Though not an exhaustive conclusion, this finding holds extensive implications for training in the organization and would pave the way for further research.